IMPLEMENTASI ALGORITMA APRIORI DALAM MENENTUKAN POLA PEMBELI CUSTOMER - Hendra Gunawan; Efori Bu'ulolo (Pusat Riset dan Inovasi Nasional, 2023)
CV. Syahfira Bakery and Cake is a business engaged in the production of cakes, pastries and bread. The more a business develops, the transactions that occur daily also increase. However, sometimes the sales transaction data is not fully utilized properly by administrative staff and company owners. In fact, if it is processed and used by administrative staff and supervised by business owners, then sales data will have a major influence on product sales in the future. Data processing can be done using data mining techniques, these data sets can produce new information, one of which is customer purchasing patterns. Syahfira Bakery and Cake is a cake, sponge and bread shop that has not fully utilized data for determining sales business strategies. With these problems, it is necessary to use transaction data to be processed with the Apriori algorithm so that it can provide new knowledge that can be utilized by shop owners. Based on the research that has been done, from the 20 processed transaction data, results are obtained that meet a minimum support of 30% and a minimum confidence of 70% and one rule is obtained, namely if a customer buys chocolate jam products, he will buy plain bread